Similar local recurrence but better function with curettage versus resection for bone giant cell tumor and pathological fracture at presentation. Issue 7 (7th February 2019) - Tsukamoto, Shinji; Mavrogenis, Andreas F.; Tanzi, Piergiuseppe; Leone, Giulio; Righi, Alberto; Akahane, Manabu; Kido, Akira; Honoki, Kanya; Tanaka, Yasuhito; Donati, Davide Maria; Errani, Costantino
Abstract: Background: There are conflicting reports for the outcome of the patients with giant cell tumor of bone (GCTB) and pathological fracture at presentation treated with curettage or resection. This study compared local recurrence, complications, and function after curettage versus resection for these patients. Materials and Methods: We retrospectively studied the files of 46 patients with histologically confirmed GCTB of the extremities admitted and treated from 1982 to 2015. The median follow‐up was 79.5 months (57.0‐125.5 months). We evaluated local recurrence and type of surgery‐related complications with imaging and function with the Musculoskeletal Tumor Society (MSTS) score. Results: Overall local recurrence was 6.5%. There were one patient with curettage and two patients with resection; local recurrence rate was similar between the two procedures but the time to local recurrence was shorter after curettage. MSTS score was significantly better after curettage. Complications occurred in two patients after curettage and in five patients after resection; because of the low number of patients with complications, a statistical comparison was not possible; however, by direct comparison of the numbers, complications were more common after resection compared with curettage. Conclusion: Curettage is recommended for GCTB and pathological fracture at presentation because of similar local recurrence but better function compared with resection. The treating physicians should be aware and inform their patients for a shorter time to local recurrence after curettage and for more complications after resection.